2014
DOI: 10.1002/ejoc.201301612
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Synthesis of N‐(Imidazo[1,2‐a]pyridin‐3‐yl)‐Substituted Sulfonamides Using Catalytic Zinc Chloride

Abstract: A one‐pot two‐step synthesis of N‐(imidazo[1,2‐a]pyridin‐3‐yl)sulfonamides from easily available arylglyoxal hydrates, 2‐aminopyridines, and sulfonamides has been developed. The procedure, using zinc chloride as catalyst, is simple and inexpensive. The desired products were obtained in moderate to good yields under the optimized reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Yu et al developed a convenient one-pot two step methodology for the synthesis of N-(imidazo[1,2-a]pyridin-3-yl)sulfonamides (27) employing arylglyoxal hydrates, 2-aminopyridines, and sulfonamides as the reactants (Scheme 10). 35 This ZnCl 2 -catalyzed reaction afforded the optimum yield in binary solvent toluene/ EtOH with a ratio of 2 : 3. Various aryl/alkylglyoxal hydrates, 2-aminopyridines, and sulfonamides were used to establish the general applicability of the method.…”
Section: From Arylglyoxal Hydratesmentioning
confidence: 97%
See 1 more Smart Citation
“…Yu et al developed a convenient one-pot two step methodology for the synthesis of N-(imidazo[1,2-a]pyridin-3-yl)sulfonamides (27) employing arylglyoxal hydrates, 2-aminopyridines, and sulfonamides as the reactants (Scheme 10). 35 This ZnCl 2 -catalyzed reaction afforded the optimum yield in binary solvent toluene/ EtOH with a ratio of 2 : 3. Various aryl/alkylglyoxal hydrates, 2-aminopyridines, and sulfonamides were used to establish the general applicability of the method.…”
Section: From Arylglyoxal Hydratesmentioning
confidence: 97%
“…Yan and Huang et al reported a Fe(II)-catalyzed tandem coupling of 2-aminopyridines and 2-methylnitroolefins (35) for the synthesis of 3-methyl-2-arylimidazo[1,2-a]pyridine derivatives (36) (Scheme 12). 37 FeCl 2 was more suitable compared to the other iron salts for this transformation.…”
Section: Tandem Coupling Between 2-aminopyridine and Nitroolefinmentioning
confidence: 99%
“…The reaction of 2-aminopyridine and α-keto imines 97.2 in ethanol afforded the desired products through a 5-exo-trig mechanism (Scheme 97). 238 Laha and co-workers developed a transition-metal-free, K 2 S 2 O 8 -mediated intramolecular oxidative amination/oxygenation of C(sp 3 )-H bonds in N-aryl benzylic amines followed by oxidation at the benzylic center for the synthesis of benzamidine or benzoxazine heterocycles. With this protocol, a sulfonamide-group-containing substrate was used for the synthesis of the sulfonyl analogues of quinazolinones.…”
Section: Other Ring-closure Reactionsmentioning
confidence: 99%
“…Owing to the importance of this heterocyclic motif, different methods for its synthesis have been developed by different groups. The important approaches adopted are: (i) condensation of 2-aminopyridines with α-diazoketones [19], α-haloketones [20], α-tosyloxyketones [21], alkynyl(phenyl)iodonium salts [22], 1-bromo-2-phenylacetylene/1,1-dibromo-2-phenylethene [23], arylglyoxal hydrates [24], propargyl alcohol [25] under different reaction conditions, (ii) tandem reactions such as reaction between Morita-Baylis-Hillman (MBH) acetates of nitroalkenes and 2-aminopyridines [26], tandem coupling between 2-aminopyridine and nitroolefin [27,28] and (iii) multicomponent reaction of 2-aminopyridine, carbonyls with nitroalkane [29,30], trimethylsilyl cyanide [31], isonitrile [32,33], imidazoline-2,4,5-trione [34,35], alkynes [36,37], alkyne carboxylic acid [38] and urea derivatives [39] (figure 2). In recent times, there have been reports of copper-catalysed synthesis for imidazo[1,2-a]pyridine derivatives also [41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, there have been reports of copper-catalysed synthesis for imidazo[1,2-a]pyridine derivatives also [41][42][43][44][45]. However, the most popular and frequently used methodology is the condensation of 2-aminopyridines with α-halocarbonyl compounds under different reaction conditions including catalysts such as Cu(OTf) 2 [19], ionic liquids [46], ZnCl 2 [24], etc. No doubt, the existing methods are useful but also possess certain limitations like longer reaction time, special apparatus, high temperature, expensive catalysts, toxic solvents and tedious workup process.…”
Section: Introductionmentioning
confidence: 99%